The Implementation of Teaching Models and the Use of Common ICT Tools for Scientific Literacy in Greece’s Second Chance Schools - Trapali, Vasiliki; Papageorgiou, Effie; Fountzoula, Christina; Karkalousos, Petros; Trapali, Maria (European Scientific Journal, ESJ, 2025)
Introduction: In recent decades, numerous studies conducted both in Greece and worldwide highlight the lack of student interest in the natural sciences, which contributes to a broader crisis in scientific literacy - including the knowledge, attitudes, and skills associated with it. Therefore, the search for appropriate teaching models, combined with the use of ICT in the educational process - particularly in the field of adult education, including Second Chance Schools (SCS) - has become a modern educational objective. Purpose: To study and statistically analyze the teaching approaches and ICT tools incorporated into their instruction by Scientific Literacy educators in Greece’s SCS, in comparison to their demographic and professional characteristics. Method: The research employed a structured questionnaire distributed via email to Scientific Literacy educators in SCS across Greece. The survey focused on three main research question groups. Using factor analysis, correlations among variables were explored, and the most significant ones were further analyzed using the chi-square test. Results: 6% of SCS Scientific Literacy educators use the “collaborative teaching” model, with 55.3% of them aged 36–45 (p<0.01). The “experimental teaching” model is avoided by 76.3% of female educators (p<0.05), 84.6% of educators under 35 (p<0.01), and 100% of those with little or no teaching experience (0–3 years) (p<0.05). 4% of educators apply inquiry-based teaching; of these, 33.3% are second-subject educators (p<0.01). Of the 39.4% who apply collaborative learning, 55.3% are aged 36–45 (p<0.05). 7% of educators with minimal or no teaching experience do not use project-based learning (p<0.05). 5% of educators use computers daily, with 56.3% being second-subject educators. 1% do not use interactive whiteboards, 72.7% of whom are physicists, chemists, or second-subject educators (p<0.05). 8% frequently use the Internet, and 38.1% of those who frequently use educational software apply differentiated instruction (p<0.05). 7% use ICT tools primarily for lesson demonstrations. Of the 47.0% who use ICT to support traditional teaching, 67.7% apply the “traditional teaching” model (p<0.01). 3% of the 34.8% who use experimental teaching use ICT tools for simulation experiments (p<0.01). Conclusion: The majority of Scientific Literacy educators in Greece’s SCS do not prefer experimental teaching and mainly use ICT tools for demonstration purposes.